The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0130093
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Women’s Facial Skin Color over the Ovulatory Cycle are Not Detectable by the Human Visual System

Abstract: Human ovulation is not advertised, as it is in several primate species, by conspicuous sexual swellings. However, there is increasing evidence that the attractiveness of women’s body odor, voice, and facial appearance peak during the fertile phase of their ovulatory cycle. Cycle effects on facial attractiveness may be underpinned by changes in facial skin color, but it is not clear if skin color varies cyclically in humans or if any changes are detectable. To test these questions we photographed women daily fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 107 publications
1
37
0
Order By: Relevance
“…This value allows us to consider whether the magnitude of total colour change is likely to be perceivable. A difference greater than 2.2 is often claimed to be the smallest noticeable under optimal lighting (Brainard, 2003;Burriss et al, 2015). However, perceptual studies of facial stimuli have shown that a difference in skin colour associated with a change in blood perfusion of 0.6 ∆E * is detectable in human skin, and a difference as small as 1.4 ∆E * is enough to influence judgements of health (Re et al, 2011).…”
Section: Skin Colourmentioning
confidence: 99%
“…This value allows us to consider whether the magnitude of total colour change is likely to be perceivable. A difference greater than 2.2 is often claimed to be the smallest noticeable under optimal lighting (Brainard, 2003;Burriss et al, 2015). However, perceptual studies of facial stimuli have shown that a difference in skin colour associated with a change in blood perfusion of 0.6 ∆E * is detectable in human skin, and a difference as small as 1.4 ∆E * is enough to influence judgements of health (Re et al, 2011).…”
Section: Skin Colourmentioning
confidence: 99%
“…In comparison to the 60 papers on non-human animals reviewed by White et al [19], researchers focusing on human colour predominantly use photography (75%), whereas researchers of non-human animal colours are most likely to use a spectrophotometer to measure colour (85%). Photography is fast, allows for distance between the researcher and the participant and permits analysis of a larger area rather than a limited number of point samples [20]. However, perhaps because photography is more accessible and perceived as a simpler process than spectrophotometry, the application and reporting of this method is often less rigorous (see also [21]).…”
Section: (B) Methods Used In Research On Human Colourmentioning
confidence: 99%
“…Jones et al [101] suggest that these colour changes may be detectable by the human visual system, given that discrimination thresholds for within-participant changes in facial redness are lower than for non-face stimuli [26]. However, in a similar longitudinal study, Burriss et al [20] found that redness was slightly heightened between ovulation and menses, with an average amplitude change of about 0.6 DE. This difference is unlikely to be perceivable by the human visual system based on the DE range where differences become perceivable [24].…”
Section: (Ii) Intra-individual Variation In Hormones and Coloration Imentioning
confidence: 99%
“…A one way analysis of variance was used to assess the impact of phase of menstrual cycle (based on the forward-counting method to allocate people to follicular, ovulation, luteal, menstrual phases) on the a* measure, given that it has previously been linked to changes in skin redness [5]. For the main analysis of the impact of oxygen, all measures were compared for each dependent variable between the two groups for the corresponding treatment time points, and as no differences were found data were collapsed to provide for a 2 (treatment) by 4…”
Section: Analysis Strategymentioning
confidence: 99%
“…Fink and colleagues [4] improved on this methodology significantly by employing digitally manipulated images of women's faces and provided supporting evidence for the "fairer sex", although interestingly strong face tone-hair colour interactions appeared of greater importance than facial skin tone alone. The colour of female facial skin has also been shown to vary in line with the ovulatory cycle, with redness increasing before ovulation and maintaining higher levels during the fertile phase [5], although the authors argue that the small variation is unlikely to be detectable by the human visual system. If the visual colour and tone of female facial skin are an honest marker of mate quality, however, it would go some way to explaining why women focus so closely on maintaining its condition and enhancing its appearance through cosmetic products and even surgical procedures [6].…”
Section: Introductionmentioning
confidence: 99%